2010
DOI: 10.1073/pnas.1005419107
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor complex is essential for Fas signal transduction

Abstract: The Fas receptor (also known as CD95 and APO-1) is a member of the tumor necrosis factor α-family of death receptors that mediate T-cell responses. Here, we show that Fas receptor signaling requires a functional T-cell receptor (TCR) complex. Fas receptor directly binds to and activates TCR components in a stimulusdependent manner. Fas receptor stimulation does not activate canonical downstream TCR pathways, but instead the TCR complex is required specifically for Fas-mediated calcium release. Importantly, nul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
4
33
1
Order By: Relevance
“…Lck is required for the most proximal Fas signaling events, including PLC-γ1 activation, proapoptotic calcium release, and cell death in T cells (20). Using a pulsed metabolic labeling and detection strategy, here we show that Lck palmitate turnover is very rapid even in resting T cells.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Lck is required for the most proximal Fas signaling events, including PLC-γ1 activation, proapoptotic calcium release, and cell death in T cells (20). Using a pulsed metabolic labeling and detection strategy, here we show that Lck palmitate turnover is very rapid even in resting T cells.…”
mentioning
confidence: 87%
“…We previously demonstrated that PLC-γ1-mediated calcium release from endoplasmic reticulum stores is required for Fas signaling (20,21). To determine whether rapid and transient palmitoylation of Lck depends on Fas-mediated elevations in cytoplasmic calcium, we used J.gamma1 (PLC-γ1 null) Jurkat cells deficient in Fasmediated calcium release (20,21). We found that basal Lck palmitoylation levels in J.gamma1 cells remained unchanged, but Fas-mediated changes in Lck palmitoylation were completely absent in this cell line (Fig.…”
Section: Fas Receptor Stimulation Leads To a Rapid And Transient Incrmentioning
confidence: 99%
See 1 more Smart Citation
“…Fas is a trans-membrane protein of tumor necrosis factor receptor superfamily (Inoue et al, 2009;Matsuda et al, 2009;Akimzhanov et al, 2010;Liedtke and Trautwein, 2012) and is expressed extensively on the cytoplasmic membrane. When Fas is bound to its ligand, the apoptotic signal may be transferred to the cells.…”
Section: Fas Expression Of Mg63 By Immunocytochemistrymentioning
confidence: 99%
“…Fas is a kind of trans-membrane protein, belonging to the super-family of TNF receptors (Moulian and BerrihAknin, 1998;O'Callaghan et al, 2008;Inoue et al, 2009;Matsuda et al, 2009;Akimzhanov et al, 2010;Liedtke and Trautwein, 2012), and can be expressed extensively on many normal and tumor tissues. When it is ligated with Fas antibody or ligand, the apoptotic signal may be transfered into cells, and the apoptosis of cells triggered by Fas pathway may be induced.…”
Section: Discussionmentioning
confidence: 99%